2019
DOI: 10.3390/app9173549
|View full text |Cite
|
Sign up to set email alerts
|

Chromium (VI) Adsorption on Modified Activated Carbons

Abstract: The paper presents the research of adsorptive properties of activated carbons to chromium (VI) removal from the water solution. Different types of carbon were investigated: WD-ekstra (WDA), WD-ekstra modified by salt acid WD(HCl) and nitrogen acid WD(HNO3). The adsorption kinetics, influence reaction, temperature and kind of carbon were determined using static methods. The adsorption of chromium (VI) onto all activated carbons was most efficient at pH 2. The time of adsorption balance for carbon WD(HCl) was 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The highly positive charge of the surface of AC strengthen the electrostatic forces between the AC and the Cr(VI) ions. By increasing the pH of the solution, the protonated surface of Ch-ACs decreases gradually and the OH − anion increases in the solution, thus an adsorption competition occurs between the anions (OH − , HCrO 4 − and CrO 4 2− ) leading to a reduction in the efficiency of the Cr(VI) ion removal [ 23 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The highly positive charge of the surface of AC strengthen the electrostatic forces between the AC and the Cr(VI) ions. By increasing the pH of the solution, the protonated surface of Ch-ACs decreases gradually and the OH − anion increases in the solution, thus an adsorption competition occurs between the anions (OH − , HCrO 4 − and CrO 4 2− ) leading to a reduction in the efficiency of the Cr(VI) ion removal [ 23 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, it was found that, at the beginning, the adsorption on Ch-ACs was fast and high for both studied heavy metal ions and this is due to the availability of pores on its surface. After some time, the adsorption decreased due to the desorption process that happens in the solution with agitation time and then increased again up to its maximum adsorption (see Figure S7 ) [ 25 , 28 ]. Figure S8 shows the equilibrium time needed for both Cr(VI) and Pb(II).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These biomass have poor adsorption and/or recovery for Cr(VI). On the other hand zeolites and activated charcoal show poor surface adsorption for Cr(VI) oxoanions, due to the characteristic electrostatic surface negative charge (Jorfi et al 2017;Puszkarewicz and Kaleta 2019;Vaid et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Another article by Kim et al [8] reported the application of alginate-coated iron hydroxide for the removal of Cu(II) and phosphate. Puszkarewicz and Kaleta [9] presented research on the adsorptive properties of activated carbon for the removal of chromium (VI) from a water solution. Sun et al [10] also reported the synthesis of a weakly basic polyacrylic anion exchanger, D311, via N-alkylation with 1-bromopropane to effectively remove nitrate from an aqueous solution.…”
mentioning
confidence: 99%